Agricultural Fast Food: Bats Feeding in Banana Monocultures Are Heavier but Have Less Diverse Gut Microbiota - Alpízar, Priscilla; Risely, Alice; Tschapka, Marco; Sommer, Simone (Frontiers in Ecology and Evolution, 2021)
Habitat alteration for agriculture can negatively affect wildlife physiology and health by decreasing diet diversity and increasing exposure to agrochemicals for animals foraging in altered landscapes. Such negative effects may be mediated by the disruption of the gut microbiota (termed dysbiosis), yet evidence for associations between habitat alteration, wildlife health, and the gut microbiota remains scarce. We examine the association between management intensity of banana plantations and both the body condition and gut microbiota composition of nectar-feeding bats Glossophaga soricina, which commonly forage within banana plantations across Latin America. We captured and measured 196 bats across conventional monocultures, organic plantations, and natural forests in Costa Rica, and quantified gut microbiome bacterial phylogenetic diversity using 16S rRNA amplicon sequencing. We found that gut microbiota from bats foraging in conventional monocultures were overall less phylogenetically diverse than those from bats foraging in organic plantations or natural forests, both of which were characterized by diverse bacterial assemblages and individualized microbiota. Despite lower diversity, co-occurrence network complexity was higher in conventional monocultures, potentially indicating altered microbial interactions in agricultural landscapes. Bats from both organic and conventional plantations tended to be larger and heavier than their forest counterparts, reflecting the higher food supply. Overall, our study reveals that whilst both conventional monocultures and organic plantations provide a reliable food source for bats, conventional monocultures are associated with less diverse and potentially dysbiotic microbiota, whilst organic plantations promote diverse and individualized gut microbiota akin to their natural forest-foraging counterparts. Whilst the long-term negative effects of anthropogenically-altered microbiota are unclear, our study provides further evidence from a novel perspective that organic agricultural practices are beneficial for wildlife health.